(untitled) (Boletin Médico de Postgrado, 2020)
We performed a study in order to propose a program for the optimization of research productivity of teachers that work in the Decanato de Ciencias de la Salud of the Universidad Centroccidental Lisandro Alvarado. The diagnostic phase investigated the need to develop a program to improve the research productivity of university teachers. The sample was 115 teachers and the results show that 43% of the respondents stated that the design of the proposal was necessary. The second phase consisted of the application of a survey to managers in order to evaluate the feasibility at the administrative, technical, institutional and socio-cultural level. The third phase corresponds to the design of the proposal which was organized with the results of the diagnostic and feasibility phase; it contains four parts: title, education, dissemination of institutional research (resources) and evaluation. This study will help raise awareness and/or motivate teachers to improve research productivity.